2009
DOI: 10.5964/ijpr.v3isupp1.71
|View full text |Cite
|
Sign up to set email alerts
|

Emotional tone in young adolescents’ close relationships and its association with deliberate self-harm

Abstract: Previous research has shown that a less positive emotional tone in adolescents' relationships to parents, but not in their relationships to peers, predicts more of behaviour problems and substance use. The purpose of the present study was to replicate these findings, and to extend this research to deliberate self-harm. In a first study with a variable-oriented approach, correlations were analysed between emotional tone in close relationships and a number of behaviour problems. The main results showed that deli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 24 publications
0
10
0
Order By: Relevance
“…Poor quality parent-child relationships characterized by a number of invalidating relational characteristics have been linked with NSSI across multiple adolescent and young adult community samples (Gratz et al, 2002;Claes et al, 2004;Gratz, 2006;Wedig and Nock, 2007;Bjärehead and Lundh, 2008;Hilt et al, 2008;Yates et al, 2008;Crowell et al, 2009b;Lundh et al, 2009;Bureau et al, 2010). Researchers have also demonstrated links between negative family environments and lapses in emotion regulating capacities.…”
Section: Invalidating Parent-child Relationships Er Difficulties Anmentioning
confidence: 94%
See 3 more Smart Citations
“…Poor quality parent-child relationships characterized by a number of invalidating relational characteristics have been linked with NSSI across multiple adolescent and young adult community samples (Gratz et al, 2002;Claes et al, 2004;Gratz, 2006;Wedig and Nock, 2007;Bjärehead and Lundh, 2008;Hilt et al, 2008;Yates et al, 2008;Crowell et al, 2009b;Lundh et al, 2009;Bureau et al, 2010). Researchers have also demonstrated links between negative family environments and lapses in emotion regulating capacities.…”
Section: Invalidating Parent-child Relationships Er Difficulties Anmentioning
confidence: 94%
“…The limited research regarding quality of peer relationships and NSSI specifically demonstrate similar results. Lundh et al (2009) showed that peer relationships characterized by poor emotional tone were correlated with a greater NSSI frequency for both boys and girls in a sample of 992 adolescents. Similarly, Hilt et al (2008) found that girls reporting poor communication with their peers were more likely to engage in NSSI when also exposed to peer victimization in a sample of 94 female middle and high school students.…”
Section: Invalidating Peer Relationships Er Difficulties and Nssimentioning
confidence: 98%
See 2 more Smart Citations
“…The frequency of deliberate self-harm behaviour was investigated using the short version of the self-report scale Deliberate Self-Harm Inventory (DSHI-9) [46] in a Swedish translation that has shown satisfactory reliability [47].…”
Section: Methodsmentioning
confidence: 99%